Heat treatment of high-pressure die casting Al-Mg-Si-Mn-Zn alloys - Trudonoshyn, Oleksandr; Randelzhofer, Peter; Körner, Carolin (Journal of Alloys and Compounds, 2021)
The microstructure and mechanical properties of Al-5.7Mg-2.6Si-0.7Mn-xZn high-pressure die casting alloys after heat treatment have been investigated. The microstructure was studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The hardness was determined by Brinell and Vickers testing. The effects of T5 (artificial ageing from the as-cast state) and full T6 heat treatment modes on the alloys with different Zn content (0.6…5 wt.%) on the microstructure and mechanical properties were investigated. The solution treatment changes the microstructure of the studied alloys. The T-AlMgZn phase dissolves into the α-Al phase during solution treatment at temperatures higher than 375ºC. Artificial ageing at 125-225ºC doesn’t lead to any changes in the microstructure of alloys, however, leads to the formation of several types of Zn-containing precipitates in the α-Al. The optimal temperature for artificial ageing from the as-cast state as well as after solution treatment is in the range 125-175ºC for 2-5 h. It was found that the most noticeable changes in the mechanical properties were achieved in the alloys with 1.2-1.8 wt.% Zn. It was found that these changes are associated with Zn distribution, the morphology of the phases and the formation of nano-sized precipitates in α-Al solid solutio
Keywords: Al-Mg-Si-Mn-Zn alloys; heat treatment; precipitation strengthening; mechanical properties